Canada's Entrepreneurs : From The Fur Trade to the 1929 Stock Market Crash: Portraits from the Dictionary of Canadian Biography - Ross, J. Andrew, 1971-; Smith, Andrew, 1976-; English, John, 1945-; Belanger, Real (Book collections on Project MUSE., 2011)
Molson. Redpath. Desjardins. Labatt. Massey. Eaton. These names are as much a part of our national identity as our hockey teams and our literature, but few of us know much about the people behind them - the individuals who have energized this country's economic life for over four centuries, and whose entrepreneurialism has shaped the face of Canadian business as we know it.This captivating collection of biographies profiles Canada's most prominent and innovative business people from the early 1600s through the first quarter of the twentieth century. Beginning with an accessible overview of the rise of entrepreneurialism in Canada, it features portraits of 61 individuals organized thematically. Here, readers will meet a variety of seminal characters: the merchants of the first trading posts and the commercial empire of the St. Lawrence; the industrialists of the Maritimes, Central Canada, and the West; the railway builders and urban developers; and everyone in between.Bringing to the fore new Dictionary of Canadian Biography research on the rise of Canadian entrepreneurialism - one of the least explored yet most important themes in our history - this book showcases Canada's long-running tradition of business innovation and growth.